Dynamics of the earth's evolution - Teisseyre, R. (Roman), 1929-; Czechowski, L.; Leliwa-Kopystynski, J., 1937- (Physics and evolution of the Earth's interior, 1993)
This sixth volume in the monograph series Physics and Evolution of the Earth's Interior presents the problems of the mature evolution of the Earth's interior. It provides comprehensive coverage of the present state of the mantle convection theory. The relations between paleomagnetism, plate tectonics and mantle convection theory are discussed. A more general view of the evolution based on the thermodynamics of irreversible processes is also given. This book will interest geophysicists, geologists, geodesists and planetologists.